2016
DOI: 10.1177/0008417416660990
|View full text |Cite
|
Sign up to set email alerts
|

Beyond research literature: Occupational therapists’ perspectives on and uses of “evidence” in everyday practice

Abstract: The findings support current literature that has suggested expanding the definition of evidence (i.e., more than research findings alone). Further investigation of evidence building in practice may help in constructing a more inclusive professional culture of evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…(Sackett et al., 1996: 77). Dougherty et al. (2016) posit that decisions are informed by a blend of therapist-internalised evidence, context and evidence from the client.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Sackett et al., 1996: 77). Dougherty et al. (2016) posit that decisions are informed by a blend of therapist-internalised evidence, context and evidence from the client.…”
Section: Discussionmentioning
confidence: 99%
“…(Sackett et al, 1996: 77). Dougherty et al (2016) posit that decisions are informed by a blend of therapistinternalised evidence, context and evidence from the client. However, while participants in this study emphasised the importance of the clients' view, they described few strategies for eliciting it.…”
Section: Collaboration With the Clientmentioning
confidence: 99%
“…It is therefore possible that these conversations might actually include aspects of EBP that are beyond levels of effectiveness or the 5‐step EBP process, but that also incorporate practical aspects related to the concrete applications of research findings in a specific context. As debates on the merits and challenges of EBP grow, 60‐62 clinicians may be turning to colleagues for discussions on topics such as the various conceptions of evidence, 63‐66 the legitimacy of patient narratives in the decision‐making process, 67 and case examples of when the evidence from gold standard designs such as randomized clinical trials conflict with patient choices and/or do not apply to their unique situation 17 . To address the issue of peer exchanges on matters pertaining to EBP, Rochette et al 58 suggested the use of professional networking to improve broader EBP competencies rather than targeting individual discrete skills.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing literature on EBP and its use among groups of health care professionals (eg, nurses, OTs, PTs, physicians) 14‐16 . In rehabilitation specifically, studies have aimed to measure and understand the constructs associated with EBP such as knowledge, confidence and actual use of EBP 9,17‐22 . For example, McEvoy et al (2010) reported a positive relationship between the amount of training in EBP and clinicians' knowledge, attitudes confidence, and use of EBP 23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation